2015
DOI: 10.1515/lpts-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Natural Radioactivity in Clay and Building Materials Used in Latvia

Abstract: This paper presents the results of natural radionuclide concentration and activity index study in materials used for construction in Latvia. Special attention is given to clay and clay ceramics. Concentrations of K-40 and Th- 232, U-238 radioactivity were determined using gamma-spectrometry method. In some building ware, maximal concentration of K-40 was 1440 Bq/kg, and of U-238 - 175 Bq/kg. In granite, the determined maximum concentration of Th-232 was 210 Bq/kg. It was found that radionuclide content in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…3). Riekstina et al [8] have shown that ac tiv ity concen tra tions of 238 U, 2 32 Th, and 40 K in clays of Lith u ania amounted to: 35, 52, and 1078 Bqkg -1 re spectively, while Todorovi} et al [9] showed that dif fer ent clays on the Ser bian mar ket had ac tiv ity con cen trations of 89 and 1303 Bqkg -1 for 232 Th and 40 K, re spectively. Com par ing the data for the clayey ma te rial of pre vi ous stud ies (tab.…”
Section: Ac Tiv Ity Con Cen Tra Tions Of Radionuclides In Soil Sam Plesmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Riekstina et al [8] have shown that ac tiv ity concen tra tions of 238 U, 2 32 Th, and 40 K in clays of Lith u ania amounted to: 35, 52, and 1078 Bqkg -1 re spectively, while Todorovi} et al [9] showed that dif fer ent clays on the Ser bian mar ket had ac tiv ity con cen trations of 89 and 1303 Bqkg -1 for 232 Th and 40 K, re spectively. Com par ing the data for the clayey ma te rial of pre vi ous stud ies (tab.…”
Section: Ac Tiv Ity Con Cen Tra Tions Of Radionuclides In Soil Sam Plesmentioning
confidence: 99%
“…By chem i cal compo si tion, clays have more ox y gen than sil i con, alu minum, or mag ne sium and can, there fore, be con sid ered hy drox ides of sil i con, alu mi num, or mag ne sium. Apart from be ing used in con struc tion, ce ram ics pro duc tion, med i cine, phar macy, and pa per in dus try, in re cent decades clays have also been ap plied as adsorbents, cat alysts or their car ri ers, ion exchangers and bleach ing mate ri als [8,9]. All the aforementioned clay ap pli ca tions are de ter mined by their spe cific prop er ties de fined by the pres ence and type of non-clay and clay min er als, organic mat ter, type and quan tity of ex change able cations, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clays represent widespread mineral wealth of great industrial significance [6]. In some types of clay, there is high content of 232 Th and 238 U above the allowed limits prescribed by the legislation [7].…”
Section: Introductionmentioning
confidence: 99%
“…The clay used in this study is from a locality in Liepa, Latvia. The clay, which has been exploited successfully for brick manufacture in the past (Dabare & Svinka, 2014;Loutou et al, 2017), was studied extensively in the 1980s-1990s, and again in the past decade (Sedmale et al, 2006(Sedmale et al, , 2017Dabare & Svinka, 2014;Riekstina et al, 2015;Loutou et al, 2017). Current research is focused on the development of new materials for which the Liepa clay might be used, such as lightweight ceramic composites with fly-ash from thermal power stations (Rugele et al, 2017), ceramic hollow spheres (Shishkin et al, 2017) and reduced-weight metalloceramic composites (Shishkin et al, 2016).…”
mentioning
confidence: 99%